China's trajectory from production to innovation: Insights from the photovoltaics sector - Carsten Gandenberger (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2018)
China's photovoltaics sector provides an interesting case to examine, if and how the country is aiming at innovation leadership after having established itself as the global manufacturing leader. Due to the dominance of Chinese companies in the global PV market, their innovation and production decisions have become crucially important for the global transition towards renewable energy. Another aspect of PV technology is that technological progress has driven the develop-ment of various types of PV cells, which can be categorised in three different technology generations. The functional analysis of the technological innovation system for PV in China conducted in this paper shows, that the government has indeed strengthened indigenous innovation efforts, which has resulted in a rapid rise of academic publications and to a lesser extent of patents for PV technology. A disaggregated analysis of transnational PV patents demonstrates that techno-logical catching-up of China picked up speed in the period between 2008 and 2010 and takes place in all three technology generations. However. technological catch-up has been most successful in the third generation of PV cells, which is still at an experimental stage and predominantly conducted at public research entities. Overall, China's PV sector seems to be still quite far from attaining global innovation leadership, which is mainly due to the relatively low engagement of the corporate sector. However, as the first generation of PV currently dominates the world market and is technologically mature, this will probably not threaten industrial leadership in the short to medium term.
urn:nbn:de:0011-n-4907573
Keywords: 330; Economic Catch-Up; Photovoltaics; Technological Innovation System; China